Electrochemically modulated liquid chromatography using a boron-doped diamond particle stationary phase - Muna, Grace W. (2008)
This paper reports on preliminary tests of the performance of boron-doped diamond powder (BDDP) as a stationary phase in electrochemically modulated liquid chromatography (EMLC). EMLC manipulates retention through changes in the potential applied (E(appl)) to a conductive packing. Porous graphitic carbon (PGC) has routinely been utilized as a material in EMLC separations. Herein the utility of BDDP as a stationary phase in EMLC was investigated and its stability, both compositionally and microstructurally, relative to PGC was compared. The results show that BDDP is stable over a wide range of E(appl) values (i.e., −1.2 to +1.2 V vs. Ag/AgCl, sat’d NaCl). The data also reveal that electrostatics play a key role in the adsorption of the aromatic sulfonates on the BDDP stationary phase, and that these analytes are more weakly retained in comparison to the PGC support. The potential for this methodology to provide a means to advance the understanding of molecular adsorption and retention mechanisms on carbonaceous materials is briefly discussed.